2021
DOI: 10.3390/ijms22084237
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Lymphangiogenic Activities and Genes Expression of Cord Blood Lymphatic Endothelial Progenitor Cells (VEGFR3+/Pod+/CD11b+ Cells) in Patient with Preeclampsia

Abstract: The abnormal development or disruption of the lymphatic vasculature has been implicated in metabolic and hypertensive diseases. Recent evidence suggests that the offspring exposed to preeclampsia (PE) in utero are at higher risk of long-term health problems, such as cardiovascular and metabolic diseases in adulthood, owing to in utero fetal programming. We aimed to investigate lymphangiogenic activities in the lymphatic endothelial progenitor cells (LEPCs) of the offspring of PE. Human umbilical cord blood LEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…One common tissue engineering-based approach involves 3D hydrogels that can support LEC spheroids (Figure 3B) to monitor lymphatic sprouting over time as an indicator of lymphangiogenic activity. [148][149][150] Alternatively, cells-LECs and stromal cells-can be encapsulated and distributed throughout 3D hydrogels, which may result in LECs forming tube-like or capillary-like structures. Encapsulated cells can also be evaluated on their migratory behavior through a 3D hydrogel that mimics an interstitial ECM or assessed for phenotypic changes in response to altered ECM properties.…”
Section: Tissue Engineered Models Of Lymphatic Vasculaturementioning
confidence: 99%
“…One common tissue engineering-based approach involves 3D hydrogels that can support LEC spheroids (Figure 3B) to monitor lymphatic sprouting over time as an indicator of lymphangiogenic activity. [148][149][150] Alternatively, cells-LECs and stromal cells-can be encapsulated and distributed throughout 3D hydrogels, which may result in LECs forming tube-like or capillary-like structures. Encapsulated cells can also be evaluated on their migratory behavior through a 3D hydrogel that mimics an interstitial ECM or assessed for phenotypic changes in response to altered ECM properties.…”
Section: Tissue Engineered Models Of Lymphatic Vasculaturementioning
confidence: 99%
“…As an important source of LEPCs, the isolation of peripheral blood cells can successfully acquire two distinguishable circulating progenitors, including classical endothelial progenitors (high-level expression of VEGFR-1 but low-level VEGFR-3) and LEPCs (high-level expression of PROX-1, VEGFR-3, Podoplanin, and LYVE-1 but low-level VEGFR-1) [ 70 ]. In addition, the existence of an analogous group (VEGFR3 + /Podoplanin + /CD11b + LEPCs) has also been confirmed in human umbilical cord blood [ 71 ].…”
Section: Stem/progenitor Cells In Postnatal Lymphangiogenesismentioning
confidence: 99%
“…Lymphatics at the maternal‐fetal interface are key factors involved in the regulation of immune cell trafficking and antigen presentation, all of which may affect the acquisition of immune tolerance during pregnancy 15–18 . In previous studies, we demonstrated that the distribution of decidual lymphatics and that the lymphangiogenic function of lymphatic endothelial cells (LECs) are reduced in PE 19,20 . LECs, which comprise lymphatic vessels in the tissue and lymph node, interact with innate and adaptive immune cells, both in the tissue and in the lymph node 21,22 .…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17][18] In previous studies, we demonstrated that the distribution of decidual lymphatics and that the lymphangiogenic function of lymphatic endothelial cells (LECs) are reduced in PE. 19,20 LECs, which comprise lymphatic vessels in the tissue and lymph node, interact with innate and adaptive immune cells, both in the tissue and in the lymph node. 21,22 LECs may help modulate inflammation and adaptive immune responses through their interactions with macrophages.…”
Section: Introductionmentioning
confidence: 99%